(untitled) (Ius Novum, 2020)
This article discusses certain issues relating to the crediting of the period of actual deprivation of liberty towards the penalty of restriction of liberty in accordance with Article 63 of the Polish Criminal Code. The author presents a method of rounding up the period of a sentenced person’s prior detention to be credited towards the penalty of restriction of liberty subsequently imposed upon him/her, which differs from the method adopted so far in the legal doctrine, while indicating that there are no grounds in the current legal state for rounding that period up to a full month and that the rounding up should only be to a full day. The paper also points to the difficulties related to the crediting of the period of actual deprivation of liberty towards the penalty of restriction of liberty resulting from the lack of coherence between the period of one year and the period of 12 months (Article 12c of the Polish Penal Enforcement Code). The article also discusses the impact that crediting of the sentenced person’s detention period under Article 63 Criminal Code has on the possibility of releasing such person from serving the remainder of his/her penalty under Article 83 Criminal Code.